The History of Science Fiction - Roberts, Adam. author. aut Link
XXII, 524 p. 18 illus.
Keywords: This book is the definitive critical history of science fiction. The 2006 first edition of this work traced the development of the genre from Ancient Greece and the European Reformation through to the end of the 20th century. This new 2nd edition has been revised thoroughly and very significantly expanded. An all-new final chapter discusses 21st-century science fiction, and there is new material in every chapter: a wealth of new readings and original research. The author’s groundbreaking thesis that science fiction is born out of the 17th-century Reformation is here bolstered with a wide range of new supporting material and many hundreds of 17th- and 18th-century science fiction texts, some of which have never been discussed before. The account of 19th-century science fiction has been expanded, and the various chapters tracing the twentieth-century bring in more writing by women, and science fiction in other media including cinema, TV, comics, fan-culture and other modes.